AMB EL COR AL PAPER. HISTÒRIA I TEORIA DE LES CARTES D’AMOR: A REVIEW ERIC HALL BORDAS - Jiménez Sureda, Montserrat (Revista Inclusiones, 2021)
Hall Bordas: Amb el cor al paper. Història i teoria de les cartes d’amor Universitat Autònoma de Barcelona Bellaterra 2020 525 pages This review appraises Amb el cor al paper. Història i teoria de les cartes d’amor by historian Montserrat Jiménez Sureda, an extensive analysis of missives throughout history. Montserrat Jiménez Sureda is a scholar in Modern and Contemporary History and currently works at Universitat Autònoma de Barcelona. This book is based on a collection of thoughts gathered throughout the process of analytical reading and comprehensive studying of an immense amount of letters. This is not a light-hearted book that delves into only love, but it anchors on what it means to portray love in letters, regardless of whom may be writing. The book is a unique scope into uncharted territory. It strives to reveal how love appears represented in the words of some of the most celebrated scientists, spiritual leaders, entertainers, authors and thought-provoking thinkers and philosophers and social scientists throughout the centuries. The review will be an overview of the practicality of this book for readers, whichever their areas of expertise may be. Jiménez Sureda mentions the huge importance this has to the field of epistolography, especially when thinking about the amount of institutionalized documentation and analysis related to modern letters documented, classified and accessible is albeit insufficient for educational purposes. This is one of the main reasons for developing this combination of thoughts and factual information which enlists, strengthens and amplifies its presence in historical studies and analysis. When entertaining love letters, one must not shy away from questioning the meaning of love itself and how it is portrayed in each case, as well as remembering romantic love is not the only one in this book.